A study of clinico-microbiological profile and outcome of urinary tract infection in diabetic kidney disease in a tertiary care hospital - Abdullah; Amir, Syed Hasan; Aslam, Mohd; Zafar, Khwaja Saifullah (International Journal of Research in Medical Sciences, 2023)
Background: this study was done to give insight about the clinical and microbiological profile of UTI in DKD and its therapeutic outcome. Methods: Patient known case of DKD presenting with signs and symptoms of UTI were included in study. Patients known case of diabetes having diabetic retinopathy and albuminuria with at least UACR of >30 mg/gm of creatinine were considered as having DKD. Results: We found, most common presenting symptom was fever, present among 35 (47.29%) patients followed by increased frequency of urination among 30 (40.54%) patients. Burning micturition and dysuria/flank pain was present among 20 (27.02%) patients and 10 (13.51%) patients respectively, lower abdominal pain in 08 (10.81%) patients. 52 (70.27%) patients’ culture were sterile and 22 (29.73%) patients’ culture were non-sterile. Out of 22 patients of non-sterile cultures, 16 (72.72%) patients have lower UTI compared to 06 (27.27%) patients with Upper UTI. E. coli was the most common organism cultured in both types of UTIs. Fungal growth (Candida tropicalis) was seen in 03 (50%) patient, all were cases of upper UTI. Conclusions: The clinical and microbiological profile of UTI in DKD doesn’t differ from UTI in diabetics and non-diabetics except for prolonged and severe course of disease. The microbiological susceptibility also doesn’t differ much. Lower age is associated with lower UTI. Upper urinary tract involvement is associated significantly with progression of CKD. Involvement of upper urinary tract should be sought in UTI in diabetics and patient with DKD and if found should be aggressively treated.